2016
DOI: 10.1097/prs.0000000000002556
|View full text |Cite
|
Sign up to set email alerts
|

Making the End as Good as the Beginning: Financial Planning and Retirement for Women Plastic Surgeons

Abstract: Financial planning is critically important to ensure financial security both during a plastic surgical career and in retirement. Unfortunately, plastic surgery training includes very little in the way of financial planning. The information that is available in the literature is mostly geared toward men. Women, with longer lifespans and more family care responsibilities, have unique needs when it comes to financial planning. Adequate attention must also be paid to life after retirement. A plastic surgical caree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Women are less likely to climb academic ranks, to reach top-level leadership positions, and to advance their careers as quickly as men. 12,15,26,27 In this study, we examined industry payments to plastic surgeons as another means of career advancement and demonstrated that female plastic surgeons receive lower payments than their male counterparts at the state and national levels, further highlighting the widespread gender disparity in plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women are less likely to climb academic ranks, to reach top-level leadership positions, and to advance their careers as quickly as men. 12,15,26,27 In this study, we examined industry payments to plastic surgeons as another means of career advancement and demonstrated that female plastic surgeons receive lower payments than their male counterparts at the state and national levels, further highlighting the widespread gender disparity in plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, women are more likely than their male counterparts to delay marriage or childbirth, and find themselves unable to retire at an early age. 12,14,15 Although recent studies suggest that improvements have been made to address these gender gaps, 10 additional studies evaluating gender inequality for other avenues of career advancement need to be performed.…”
mentioning
confidence: 99%
“…10 There is also interest in career planning and retirement planning for plastic surgeons at all levels of practice; retired surgeons could certainly provide helpful perspective to this end. 11,12 Although these ideas ultimately require buy-in from all parties involved, this study clearly demonstrates that there are many retired surgeons who are amenable to effective, efficient channels of connection and idea exchange with the greater plastic surgery community.…”
Section: Discussionmentioning
confidence: 87%
“…As shown in table 2, each of these articles addressed general financial planning principles and/or a variable number of finance topics, such as debt/liabilities, savings/assets, investing, budgeting, money basics (eg, time-value of money, discounting and compounding), contract negotiation, selecting and interacting with financial advisors, children’s college savings plans, insurance (life, disability, property and casualty), retirement planning, estate planning and taxes. The number of topics discussed in each article varied, with two articles addressing only general financial planning,35 39 while seven covered 10 or more topics 9 10 22 25 38 55 56. The most covered topic was debt (90%), followed by retirement planning (78%), budgeting (67%) and investing (65%).…”
Section: Resultsmentioning
confidence: 99%